SOCIAL CAPITAL OF THE SMALL INDUSTRY OF TRADITIONAL CHILI ANCHOVY CHIP SIBOLGA (Case Study of the Marketing Network of Traders of Traditional Chili Anchovy Chip Sibolga) - Josua Ryandi Sibuea; Grace Prima Apriani Sihombing; Silvia Annisa (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study analyzes the role of social capital in the small scale chili chip industry in Sibolga, with a focus on marketing networks. Sibolga City’s coastal tourism attracts many visitors and creates economic opportunities for local communities, including the production of chili chips as a local specialty. The sustainability of this industry depends on cooperation among actors involved in production and distribution. This research uses a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. The findings show that social capital in the Sibolga chili chip industry consists of trust, norms, and networks. Trust is built among raw material suppliers, distributors, and consumers through long-term relationships. Norms help maintain price stability and preserve the uniqueness of product recipes. Networks connect raw material suppliers with small-scale producers. These forms of social capital play an important role in supporting the marketing network and sustainability of the Sibolga chili chip industry.